AN ANALYSIS OF FIGURATIVE LANGUAGE USED IN BETHEL MUSIC’S SELECTED SONG LYRICS - Diun, Vinsensia Susanti; Winarta, Ida Bagus Gde Nova (ID Solutions, 2023)
Music is a medium of artistic expression and reflects supporting community culture. The music contains the lyrics distinctive features, which are meant to be accessible to music lovers in the whole world. This study is aimed to answer two problems of the study, they are: (1) To identify the types of figurative languages found in Bethel Music’s song lyrics, (2) To analyze and describe the meaning of the figurative language used in Bethel Music’s song lyrics. The writer used theory from Arp & Perrine (1963) too identify the types of figurative language and the theory from Leech (1981) to analyze the meaning of figurative language. This study was used qualitative method to find out the types of figurative language and to analyzed the meaning of figurative language in Bethel Music’s song lyrics. There is simile, metaphor, personification, synecdoche, metonymy, symbol, hyperbole. Based on the data, there are 35 lyrics that contains figurative language. The detail results are 6 similes (17,14%), 14 metaphors (40,00%), 7 personifications (20,00%), 1 synecdoche (2,86%), 1 metonymy (2,86%), 3 symbols (8,57%), and 3 hyperboles (8,57%). The dominant type that found from the song lyrics is metaphor (40,00%) and the low frequent used are synecdoche and metonymy (2,57%).